The Potential for Dietary Modification of Islet β-Cell Homeostasis in Autoimmune Diabetes - Gen-Sheng Wang; Lisa M. Kauri; Fraser W. Scott (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2007)
Type 1 diabetes (T1D) results when an immune attack destroys most of the insulin-producing β-cells in the pancreas, overwhelming the capacity of the organ to preserve normoglycemia. Islet homeostasis is maintained by a physiological balance of β-cell neogenesis, replication and death. This balance is affected by various challenges such as food consumption, nutrient uptake, hormonal status, obesity and pregnancy. It is the susceptibility to develop T1D that is inherited and disease expression is strongly influenced by exposure to common environmental factors. It is well accepted that diabetes incidence can be altered in diabetes-prone animals by modification of dietary components. This raises the possibility that diet-associated changes in islet function or mass play a role in T1D. In this review, we discuss the effect of diet on islet β-cell homeostasis, with particular emphasis on islet neogenesis and replication in healthy and diabetes-prone animals with a brief discussion of human studies. A better understanding of the role of diet on islet homeostasis in susceptible individuals may help develop strategies for prevention and treatment of diabetes by dietary intervention.
Keywords: type 1 diabetes